A morte é mesmo o fim de tudo? Herança digital e transmissão post mortem dos bens digitais em face dos direitos da personalidade - Naves, Gabriela Gomes dos Santos (2024)
Given the growing influence of technology, the concept of digital assets has become relevant in inheritance law, especially in relation to the post-mortem transmission of these assets. The central problem is the legislative gap that regulates the succession of these assets, given that current legislation has not kept pace with technological advances. The general objective of the research is to analyze the possibility of transferring digital assets in the context of succession, taking into account privacy rights and the lack of specific rules. The specific objectives include an examination of technological transformations, the conceptualization of digital inheritance, an analysis of personality rights and an evaluation of current bills dealing with the subject. The methodology used was bibliographical research, based on reading scientific articles, dissertations, doctrines and legislation. The approach is qualitative, with an emphasis on the logical-deductive method. The justification for the study lies in the growing importance of digital assets, which can become a significant component of the inheritance. In addition, the lack of specific regulations on the subject presents challenges for inheritance law, especially with regard to the balance between the transmission of assets and the protection of the deceased's personality rights. The results of the research indicate the urgent need for specific regulations on digital inheritance, given that digital assets have both patrimonial and personal value, and their destination after the death of the owner is an issue that requires special attention from the legislator. The dissertation concludes that the creation of specific regulations is essential to guarantee legal certainty in the transmission of these assets and to protect the rights of the heirs and the deceased.